Peran Putusan Mahkamah Konstitusi dalam Perlindungan Hak Asasi Manusia terkait Penyelenggaraan Pemilu - M. Gaffar, Janedjri (Mahkamah Konstitusi Republik Indonesia, 2013)
Constitution, as the supreme law, is created to protect human rights. Constitution contains basic principles of state administration and citizens rights that have to be protected. In relation to the citizens political rights, election is related to Human Rigts matters. Election administration constitutes manifest acknowledgement of human rights in the life of the nation. Democratic election can be carrried out if there protection of human rights is guaranteed. One of the holders of judicial power that plays roles in providing human rigths protection through its decision is Constitutional Court (CC). The Court carries out the function as the guardian of the constitution, the final interpreter of the constitution. Besides, the Court also functions as the guardian of democracy, the protector of citizens’ constitutional rights and the protector of human rights. The function of the Court as the protector of human rights constitute consequence of the incorporation of Human Rights as the substance of the constitution. The endeavour of the Court to protect human rights can be perceived from some of its decisions either in the case of judicila review of laws or settlement of local election disputes which are, inter alia, restoration of the right to vote for the former members of Indonesian Communist Party, the right to vote for certain ex-prisoners, the granting of rights to be candidate for parties that do not have seat in the parliament, the right to be candidate for individual independent citizen in local election, protection of rights for incumbents, the right to vote that is free from threat and terror, protection of the right to be candidate thta is free from the act of impediment and recognition of mechanisms that are recognized in customary law.